Malaysia Halal Certification: A Review of Behavioural Intention in Adoption of Halal Auditing Mobile Apps - Nur Aaina Athira Hamdan,; Siti Suhana Jamaian, (Journal of Applied Science, Technology and Computing, 2024)
The increasing global demand for halal products has driven the need for more efficient and transparent halal certification processes, particularly in Malaysia. However, adopting digital tools, such as halal auditing mobile apps, remains underexplored. This study aims to examine the behavioral intention to adopt halal auditing mobile apps using the Unified Theory of Acceptance and Use of Technology (UTAUT) model, focusing on key factors such as performance expectancy, effort expectancy, social influence, and facilitating conditions and indirect factors such as anxiety, self-efficacy and attitude towards using technology. The study highlights that while mobile apps can significantly enhance efficiency and reduce errors in halal auditing, challenges exist in integrating religious and cultural aspects into the adoption process. The findings underscore the need for more specific research on the regulatory and operational needs of halal certification in Malaysia. These insights can guide future research and help practitioners implement digital innovations in halal auditing